The epidemic wave of influenza A (H1N1) in Brazil, 2009 A onda epidêmica de Influenza A (H1N1) no Brasil, 2009 - Cláudia Torres Codeço; Josiane da Silva Cordeiro; Arthur Weiss da Silva Lima; Rodrigo Amarante Colpo; Oswaldo Gonçalves Cruz; Flavio Codeço Coelho; Paula Mendes Luz; Claudio José Struchiner; Fernando Ribeiro de Barros (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
This study describes the main features of pandemic influenza A (H1N1) in Brazil during 2009. Brazil is a large country that extends roughly from latitudes 5ºN to 34ºS. Brazil has tropical and sub-tropical climates, a heterogeneous population distribution, and intense urbanization in the southern portions of the country and along its Atlantic coast. Our analysis points to a wide variation in infection rates throughout the country, and includes both latitudinal effects and strong variations in detection rates. Two states (out of a total of 23) were responsible for 73% of all cases reported. Real time reproduction numbers demonstrate that influenza transmission was sustained in the country, beginning inMay of 2009. Finally, this study discusses the challenges in understanding the infection dynamics of influenza and the adequacy of Brazil's influenza monitoring system. Este estudo descreve a primeira onda de influenza A (H1N1) no Brasil, um país que se estende entre as latitudes 5ºN e 34ºS, caracterizado por climas tropicais e subtropicais, com distribuição populacional heterogênea e intensa urbanização ao longo da costa e na região sul-sudeste. Nossa análise indica grande variação geográfica nas taxas de ataque no país, com efeitos longitudinais e variação na taxa de detecção. Dois estados foram responsáveis por 73% de todos os casos registrados: São Paulo e Paraná. O número reprodutivo em tempo real demonstra que a transmissibilidade se sustentou no país desde maio de 2009 até pelo menos agosto de 2009. Este trabalho por fim discute os desafios de estudar e monitorar doenças emergentes de sintomatologia inespecífica, como a influenza, e a adequação do sistema de vigilância.